Chloride on the Move. (March 2017) - Li, Bo; Tester, Mark; Gilliham, Matthew
Abstract : Chloride (Cl − ) is an essential plant nutrient but under saline conditions it can accumulate to toxic levels in leaves; limiting this accumulation improves the salt tolerance of some crops. The rate-limiting step for this process – the transfer of Cl − from root symplast to xylem apoplast, which can antagonize delivery of the macronutrient nitrate (NO3 − ) to shoots – is regulated by abscisic acid (ABA) and is multigenic. Until recently the molecular mechanisms underpinning this salt-tolerance trait were poorly defined. We discuss here how recent advances highlight the role of newly identified transport proteins, some that directly transfer Cl − into the xylem, and others that act on endomembranes in 'gatekeeper' cell types in the root stele to control root-to-shoot delivery of Cl − . Trends: Cl − toxicity is a major component of crop salt stress that has been relatively neglected compared to the effects of Na + . Reducing Cl − concentration in the xylem is a key step for reducing Cl − toxicity, with loading of Cl − to the root xylem being a rate-limiting gatekeeper step. Several Cl − transporters involved in modulating net transfer of Cl − to the root xylem have been identified recently; some are present the plasma membrane whereas others are on endomembranes. Our knowledge of the molecular regulation of cellular Cl − efflux to the root xylem (ABA-downregulated) lags behind that of Cl − efflux in stomatal guard cells, which is upregulated by ABA and modulates stomatal closure.